Analysis of electrocoagulation process efficiency of compost leachate with the first order kinetic model - Simonič, Marjana (Array, 2020)
Large quantities of leachate are generated from the water release during the decomposition of the biodegradable waste. The composition of compost leachate is very complex and its treatment is necessary before releasing into the environment. The possibilities of treating compost leachate by electrocoagulation have been extensively studied. The scope of this work was to investigate applicability of the first order kinetic model for degradation of metal and organic compounds from compost leachate by electrocoagulation process. Experimental results showed 75 % removal efficiency of Cu2+ and 65 % of Zn2+, while chemical oxygen demand was reduced by 36 %. According to obtained kinetic parameters, simulation of metal removal efficiency was performed in batch reactor. This way optimal electrocoagulation time which is needed for 95 % efficiency of metal removal was determined at 120th min for Zn2+ and 102nd min for Cu2+.